2017
DOI: 10.3354/esr00852
|View full text |Cite
|
Sign up to set email alerts
|

Sawfish (Pristidae) records along the Eastern Amazon coast

Abstract: Sawfishes are the most endangered cartilaginous fishes on the planet. Their external morphology facilitates entanglement in fishing nets and their K-selected life history hinders the recovery of exploited populations. The Eastern Amazon coast (EAC) is known to be an area where sawfishes occur in Brazil, but few studies have been conducted in the area to better understand their biology and ecology. The present study reports sawfish captures along the coast of Brazil's second largest state. Data were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
1
16
0
4
Order By: Relevance
“…Among the respondents the total length also varied, 85% said the lengths were about 3.0 m where as 15% said that the length was < 3.0 m. Hossain et al (2014) and Bonfil (1994) reported that the sawfish are caught as a by-catch from other fisheries by using bottom and drift gill nets. According to Dulvy et al (2016) and Feitosa et al (2017), sawfish are susceptible to bycatch through entanglement of their rostra in the net, which also supported by the statement of the respondents (95%).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Among the respondents the total length also varied, 85% said the lengths were about 3.0 m where as 15% said that the length was < 3.0 m. Hossain et al (2014) and Bonfil (1994) reported that the sawfish are caught as a by-catch from other fisheries by using bottom and drift gill nets. According to Dulvy et al (2016) and Feitosa et al (2017), sawfish are susceptible to bycatch through entanglement of their rostra in the net, which also supported by the statement of the respondents (95%).…”
Section: Resultssupporting
confidence: 53%
“…All the five sawfish species are facing different categories of threats (CITES 2013, Dulvy et al 2016. Sawfishes are distributed in shallow, sandy or muddy bottoms across the coastal areas, estuaries and freshwaters from the tropical to sub-tropical regions (Roy et al 2012, Faria et al 2013, Feitosa et al 2017. Sawfishes are identified as a very large shark-like rays and are able to tolerate a wide range of salinities specially mangroves Dulvy 2014, Leeney 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some elasmobranch species, such as the Bull Shark Carcharhinus leucas and Largetooth Sawfi sh Pristis pristis , are known to use coastal areas in northern South America, including estuaries and rivers affected by cyclical salinity changes (Thorson 1972 ;Cervig贸n and Alcal谩 1999 ;Feitosa et al 2017 ). Particular areas of the Amazon have a stronger infl uence of sea currents during the drought months with the occurrence of tidal bores (Kjerfve and Ferreira 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…Historical populations in Lake Nicaragua and reports as far upstream as Manaus in the Amazon river indicate the extent of freshwater use of largetooth sawfish (Thorson 1982, Burgess et al 2009). Yet the patterns of sawfish use of brackish and fresh water are not well understood, and many published accounts are limited to opportunistic sightings (Nunes et al 2016, Feitosa et al 2017, Schmid and Giarrizzo 2017. Uncovering these patterns of habitat use and migration could help target conservation and management actions to life-stages, locations, or seasons where the risk to sawfish is greatest.…”
Section: Introductionmentioning
confidence: 99%